Evaluation of Training Load During Suspension Exercise. Issue 8 (August 2021) - Giancotti, Giuseppe Francesco; Fusco, Andrea; Varalda, Carlo; Capelli, Giovanni; Cortis, Cristina
Abstract : Abstract: Giancotti, GF, Fusco, A, Varalda, C, Capelli, G, and Cortis, C. Evaluation of training load during suspension exercise. J Strength Cond Res 35(8): 2151–2157, 2021—The aims of this study were to evaluate body inclination and ground reaction force and to predict equations to estimate the training load distribution during suspension training (ST) static back-row at different lengths of the straps. Thirty volunteers (men = 16 and women = 14; age = 23.3 ± 1.7 years; body mass = 63.9 ± 13.3 kg; height = 167.9 ± 9.2 cm; body mass index [BMI] = 22.5 ± 3.4 kg·m −2 ) performed 14 static back-rows at 7 different lengths of the straps in 2 different elbow positions (flexed and extended). When the length of the straps increased, ground reaction force and body inclination decreased. Moreover, in the flexed elbow position, higher ground reaction force values were recorded with respect to the extended one. Two multilevel regression models ( p < 0.05) were created. In the first one, ground reaction force was used as a dependent variable, whereas body inclination angle, body mass, height, BMI, and elbow position were used as independent variables. Significant ( p < 0.05) effects were found for all variables included in the model, with an intraclass correlation coefficient (ICC) of 0.31. In the second model, the body inclination angle was replaced by the length of the ST device. Significant ( p < 0.05) effects were found also in the second model for all variables included, with an ICC of 0.37. The proposed models could provide different methods to quantify the training load distribution, even if the use of the straps' length could result easier and faster than body inclination angle, helping practitioners and instructors to personalize the workout to reach specific purposes and provide load progression.